Agro-morphological diversity (quantitative traits) of rice (Oryza sativa L.) cultivated in Baglung District, Nepal - Pathak, Hom Nath (Himalayan Biodiversity, 2018)
Agro-morphological traits are the features of cultivated rice i.e. Oryza sativa L. Rice landraces differ from the other landrace in morphological features such as grain weight, culm number, and height of the plant. Nineteen different landraces of cultivated rice from Paiyunpata village, Baglung were studied and their quantitative characters were measured. The most varied landraces in morphological characters (Khate, Rato, Nepale, Anadi etc. i.e. species far from quadrants in PCA) are suggested for crop improvement. Findings from this research could be helpful for germplasm conservation.